Accuracy of Grading Gleason Score 7 Prostatic Adenocarcinoma on Needle Biopsy: Influence of Percent Pattern 4 and Other Histological Factors. Issue 6 (3rd February 2017) - Meliti, Abdelrazak; Sadimin, Evita; Diolombi, Mario; Khani, Francesca; Epstein, Jonathan I.
Abstract : BACKGROUND: Recognition of Gleason pattern 4 in prostatic needle biopsies is crucial for both prognosis and therapy. Recently, it has been recommended to record percent pattern 4 when Gleason score 7 cancer is the highest grade in a case. METHODS: Four hundred and five prostate needle core biopsies received for a second opinion at our institution from February–June, 2015 were prospectively diagnosed with prostatic adenocarcinoma Gleason score 7 as the highest score on review by a consultant urological pathologist. Percentage of core involvement by cancer, percentage of Gleason pattern 4 per core, distribution of Gleason pattern 4 (clustered, scattered), morphology of pattern 4 (cribriform, non‐cribriform), and whether the cancer was continuous or discontinuous were recorded. RESULTS: Better agreement was noted between the consultant and referring pathologists when pattern 4 was clustered as opposed to dispersed in biopsies ( P  = 0.009). The percentage of core involvement by cancer, morphology of pattern 4, and continuity of cancer did not affect the agreement between the consultant and referring pathologists. There was a trend ( P  = 0.06) for better agreement based on the percent of pattern 4. CONCLUSIONS: When pattern 4 is scattered amongst pattern 3 as opposed to being discrete foci, there is less interobserver reproducibility in grading Gleason score 7 cancer, and in this setting pathologists should consider obtaining second opinions either internally within their group or externally. Prostate 77: 681–685, 2017 . © 2017 Wiley Periodicals, Inc.